Applications and challenges of silicon-based optoelectronics in communication - Dezhao LI; Pengfei XU; Kejian ZHU; Zhiping ZHOU (Dianxin kexue)
Silicon-based optoelectronics technology has the advantages of photonics, such as broadband, high-speed and anti-interference, as well as the advantages of microelectronics, such as large-scale integration, low energy consumption and low cost.Silicon-based optoelectronics is showing superior advantages in high-speed and short-reach communications and posing a challenge to the conventional indium phosphide (InP) optical modules.The application, development and technical challenges of silicon-based optoelectronics technology in communications were briefly discussed.There is an urgent need to develop high performance devices, packaging technology, automation software for further development of the silicon-based optoelectronic technology.